THE EFFECT OF FINANCIAL RATIO ON FINANCIAL DISTRESS IN INDONESIA SHARIA COMMERCIAL BANKS - Hananiyah, Wardah Mujadidah; Jaya, Tiara Juliana (I-Finance Journal, 2023)
An early warning system can be implemented to anticipate the presence of financial distress, which will threaten financial problems. Altman Z-score is a tool for predicting a company's bankruptcy level by calculating several financial ratios. This study aimed to see whether finances can affect financial distress in Indonesian Islamic Banks. This study used Eviews software version 10 with panel data analysis techniques. The research object is the Indonesian Sharia Commercial Bank, which published semiannual financial reports from 2017-2022. Based on information on the official OJK website, there are 12 Islamic Commercial Banks, but only 9(nine) banks meet the sample criteria in this study. The results of the study show that ROA and CR have a significant positive effect on financial distress. Meanwhile, ROE and DER have a significant negative effect on financial distress. Unlike the case with NPF, which has no significant effect on financial distress.